1979
DOI: 10.1084/jem.150.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of an antibody response via network-induced auto-anti-idiotype

Abstract: The antibody response of a single outbred rabbit was studied throughout three rounds of injections with Micrococcus lysodeikticus vaccine over a 31-mo period. The first-round response was characterized by a vigorous anti- micrococcus response and a strong anti-IgG rheumatoid factor response. The second-round response consisted of a triad of interacting molecules: anti- micrococcal antibodies, autoanti-idiotypic antibodies specific for distinct clonotypes of the first-round anti-micrococcal antibodies, and Fc-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Strayer et al (37,38) have shown in the T15 system that antiidiotype suppression is long-lasting in the neonate but that it only exerts transient suppression in adults. Other studies from this lab (19) have verified the reversibility of natural auto-antiidiotype regulation in rabbits and the data from the experiment described in Fig. 5 suggest that the natural auto-antiidiotypic regulation that followed the natural antiallotype response was reversible.…”
Section: Stimulation Of Anti-al Synthesismentioning
confidence: 72%
See 2 more Smart Citations
“…Strayer et al (37,38) have shown in the T15 system that antiidiotype suppression is long-lasting in the neonate but that it only exerts transient suppression in adults. Other studies from this lab (19) have verified the reversibility of natural auto-antiidiotype regulation in rabbits and the data from the experiment described in Fig. 5 suggest that the natural auto-antiidiotypic regulation that followed the natural antiallotype response was reversible.…”
Section: Stimulation Of Anti-al Synthesismentioning
confidence: 72%
“…It is tempting to speculate that the cross-reactive idiotopes found in this paper and in (19) and (35) that seem to be involved in idiotype regulation in normal outbred animals may be similar to, or identical with, the special class of regulatory idiotopes postulated by Paul and Bona (39). These idiotopes in (35) were found only in sera of rabbits which mounted auto-antiidiotypic responses.…”
Section: Stimulation Of Anti-al Synthesismentioning
confidence: 88%
See 1 more Smart Citation
“…It has also been shown in inbred as well as outbred animals that autoantiidiotypic antibodies arise during the course ofthe normal immune response and regulate idiotype expression (26)(27)(28). Thus, it is not unlikely that antiidiotypic antibody can inhibit antibody synthesis by normal B cells, and experiments in our laboratory indicate that antiidiotypic antisera to human antitetanus toxoid antibodies precisely do so (7).…”
Section: Methodsmentioning
confidence: 85%
“…The discovery of positive and negative interactions between T and B lymphocytes (7) and the possible involvement of idiotypes in clonal interactions (4) indicate that the immune system can recognize selfand is regulated by a complex idiotypic network (1)(2)(3)(4)(5). Idiotypes and autoantiidiotypes coexist in the repertoire of a single individual; autoantiidiotypes can be induced or occur spontaneously during the immune response (4,(25)(26)(27). These antiidiotypic antibodies can exert either positive or negative influences on antibody biosynthesis or on effector cell function (10,27 In this report we have examined the modulation of autoantibody activity by means of antiidiotypic antibodies.…”
Section: Resultsmentioning
confidence: 99%